Efektifitas Terapi Musik Terhadap Penurunan Kecemasan Pada Postpartum Blues : Literature Review - Feva Tridiyawati; Fitri Wulandari (Universitas Malahayati Lampung, 2022)
ABSTRACT The postpartum period is a transitional period for mothers because many changes occur, both physically, psychologically, emotionally and socially. Postpartum blues are feelings that occur in postpartum mothers which are characterized by anxiety, panic attacks, fatigue, feelings of self-blame and feeling unable to take care of their baby. The purpose of this review article is to determine the effectiveness of music therapy on reducing anxiety in Postpartum Blues based on previous studies. In this article review, the author uses three databases, namely using PuBmed, Cochrane and Google scholar to find articles according to the inclusion and exclusion criteria, then a review is carried out. The research design included in this literature review uses a quasi-experimental design and a random control trial, the search years 2012-2022. The findings of this review article are an analysis of the effectiveness of appropriate music therapy used in reducing anxiety due to postpartum blues. There are several music therapies that are effective in preventing or overcoming postpartum blues, including not only using classical Mozart music but also being able to use musical music therapy, keroncong,